Epidemiologic and Pathologic Aspects of Feline Eosinophilic Granuloma Complex - Ehlers, Luiza Presser; Slaviero, Mônica; Piccolo Vargas, Thainã; Argenta, Fernando Froner; Driemeier, David; Amorim da Costa, Fernanda Veiria; Pavarini, Saulo Petinatti; Sonne, Luciana (Acta Scientiae Veterinariae, 2019)
Background: The feline eosinophilic granuloma complex (FEGC) includes a group of lesions that affect the skin, mucocutaneous junctions, and oral cavity of cats. It comprises three distinct clinical entities: the eosinophilic ulcer (EU), the eosinophilic plaque (EP) and the eosinophilic granuloma (EG). The EU is usually found in the upper lip. Lesions of EP occur most commonly on the abdomen and medial thigh. The EG lesions usually appear on the tongue and hard palate. The aim of this study is to describe the localization and pathological findings of FEGC through a retrospective study and testing by immunohistochemistry if feline herpesvirus type 1 (FHV-1) infection may be associated. Materials, Methods & Results: The records of biopsy specimens from the Department of Veterinary Pathology of the Universidade Federal do Rio Grande do Sul were recovered and cats diagnosed with FEGC were selected since January 2006 to December 2017. General data, such as age, sex, breed and distribution lesions, were analyzed and compiled. The histological slides were reviewed by optical microscopy and the microscopic findings were detailed. Sections of tissue were used in immunohistochemistry to investigate the presence of feline herpesvirus-1 (FHV-1) using anti-FHV-1 antibody. In this study, 30 cats were diagnosed with FEGC. Most part of the cats were mixed breed (27/30), and there were no sex predisposition. The age of the cats ranged from seven months to 13 years old, and the median was three years. The lesion distribution of FEGC was 40% in oral cavity, 33.3% in skin and 26.6% in mucocutaneous junction. Histologically, the main lesion of all distributions was characterized by diffuse dermal/submucosa inflammatory infiltrate composed of eosinophils. Within the inflammation there were large irregular foci of collagen fibers and degranulated and degenerating eosinophil (“flame figures”). Oftentimes these foci were surrounded by macrophages and fewer multinucleated histiocytic giant cells. There were mild to moderate inflammatory infiltrate of mast cells, lymphocytes and plasm cells in dermis and submucosa. Ulceration of epidermis and mucosa were observed in majority of FEGC lesions with inflammatory infiltrate of neutrophils. All cases were negative for FHV-1 in the immunohistochemical evaluation. Discussion: In this study, feline eosinophilic granuloma complex was uncommon, accounting 0.96% of the feline cases diagnosticated in 15 years. Agreeing with the other authors, there was no sex and breed predilection. The median of age were three years old, some authors report higher occurrence in young animals and associated with genetic predisposition. Histologically, the most frequent findings were submucous and dermal inflammatory infiltrate composed primarily of eosinophils associated with areas of “flame figures”. Surrounded these areas, there were intense inflammatory infiltrate composed of macrophages, palisading macrophages and fewer multinucleated histiocytic giant cells as previously described by other authors. The ulceration of epidermis and mucosa was a common finding of eosinophilic granuloma complex lesions especially in cases where the oral cavity was affected. In this study, we could not evaluate the presence of FHV-1 in feline cases of eosinophilic granuloma complex. The area commonly affected in cases of FEGC was the oral mucosa. It may be due to differentiate from other diseases that affect the same area. Feline eosinophilic granuloma complex are important differential diagnosis for other diseases that include neoplasms, especially squamous cell carcinoma.